O conto contemporâneo de Marina Colasanti: estilhaços do maravilhoso na viagem das "23 histórias" - Rocha, Vanessa de Bello Lins da (2010)
This paper analyzes ten stories of 23 histórias de um viajante, Marina Colasanti, from the rescue and return of gender and the wonderful tradition held by the author to write his fictional worlds. By revisiting the wonderful tales, reinterpreted and violates some elements of tradition in the light of contemporary, among them the metamorphosis, the journey and the fairies. Note also through writing Colasantiana, especially in the book 23 histórias de um viajante, this attempt to rescue the traditional root, because the stories are connected to a frame story, which leads to the classic example of construction of the As Mil e uma Noites but that story frame is frequent dialogue with the reader, and it is as if the twenty-fourth story in the book, because it depends on the other 23 stories, moreover all the stories are interrelated, allowing the book to be read in sequence or random. The author also innovates to try to put the existential dilemma of his characters in the service of the dilemma of literary construction. The theoretical framework that supports the reading of the wonderful is Todorov, Marino, Chiampi, Rodrigues and Le Goff, and as for fairy tales has Propp and Jolles as main theoretical. The methodology used for the reading of the corpus is the descriptive and analytical